The Anti-Inflammatory and Antimicrobial Potential of Selected Ethnomedicinal Plants from Sri Lanka - Mayuri Napagoda; Jana Gerstmeier; Hannah Butschek; Sudhara De Soyza; Simona Pace; Sybille Lorenz; Mallique Qader; Sanjeeva Witharana; Ajith Nagahawatte; Gaya Wijayaratne; Aleš Svatoš; Lalith Jayasinghe; et al. (Molecules, 2020)
Traditional folk medicine in Sri Lanka is mostly based on plants and plant-derived products, however, many of these medicinal plant species are scientifically unexplored. Here, we evaluated the anti-inflammatory and antimicrobial potency of 28 different extracts prepared from seven popular medicinal plant species employed in Sri Lanka. The extracts were subjected to cell-based and cell-free assays of 5-lipoxygenase (5-LO), microsomal prostaglandin E2 synthase (mPGES)-1, and nitric oxide (NO) scavenging activity. Moreover, antibacterial and disinfectant activities were assessed. Characterization of secondary metabolites was achieved by gas chromatography coupled to mass spectrometric (GC-MS) analysis. n-Hexane- and dichloromethane-based extracts of Garcinia cambogia efficiently suppressed 5-LO activity in human neutrophils (IC50 = 0.92 and 1.39 µg/mL), and potently inhibited isolated human 5-LO (IC50 = 0.15 and 0.16 µg/mL) and mPGES-1 (IC50 = 0.29 and 0.49 µg/mL). Lipophilic extracts of Pothos scandens displayed potent inhibition of mPGES-1 only. A methanolic extract of Ophiorrhiza mungos caused significant NO scavenging activity. The lipophilic extracts of G. cambogia exhibited prominent antibacterial and disinfectant activities, and GC-MS analysis revealed the presence of fatty acids, sesquiterpenes and other types of secondary metabolites. Together, our results suggest the prospective utilization of G. cambogia as disinfective agent with potent anti-inflammatory properties.